The Effect of Using Grammarly on EFL Students’ Writing Accuracy: A Quasi-Experimental Research - Hidayat, Agus; Sari, Ratna (Raden Intan State Islamic University of Lampung, Indonesia, 2025)
This study aims to investigate the effect of using Grammarly, an automated writing evaluation (AWE) tool, on the writing accuracy of EFL students in an Indonesian higher education context. Addressing the persistent challenges of grammatical accuracy in EFL writing, the study explores how technology can supplement traditional instruction to improve learner outcomes. Employing a quasi-experimental pre-test/post-test non-equivalent group design, the research involved 60 EFL students divided into experimental and control groups. The experimental group used Grammarly during writing tasks, while the control group received conventional instruction without digital assistance. Data were collected through structured essay writing tasks evaluated with an analytic rubric, and analyzed using descriptive and inferential statistics, including t-tests and ANOVA. The results revealed a statistically significant improvement in the writing accuracy of the experimental group compared to the control group. The experimental group showed an average gain score of 19.9 points, while the control group showed only 0.4 points. Notable reductions in grammatical errors were observed, particularly in article usage, verb tense consistency, and punctuation. The findings indicate that Grammarly effectively enhances writing accuracy, especially among lower-proficiency learners, supporting its integration into EFL writing instruction as a complementary tool.